2016
DOI: 10.1021/acscatal.5b02386
|View full text |Cite
|
Sign up to set email alerts
|

Organic Synthesis Enabled by Light-Irradiation of EDA Complexes: Theoretical Background and Synthetic Applications

Abstract: In the past decades, the physicochemical properties of electron donor−acceptor, EDA, complexes (also called charge-transfer, CT, complexes) have been extensively studied, although their synthetic applications have been somewhat limited. However, in recent years, this scenario has started to change as an increasing number of examples have been reported. In this regard, this review aims to present and discuss the main aspects associated with the physicochemical properties of these complexes and a selection of sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
351
1
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 571 publications
(367 citation statements)
references
References 160 publications
(147 reference statements)
10
351
1
5
Order By: Relevance
“…The combination of 1, 2 , and TFAA (1:1:2 ratio; Figure 2A) revealed a strongly absorbing signal in the visible region, and we postulated that this new absorbance could be attributed to an electron donor-acceptor (EDA) interaction. 71 To probe this relationship further, we measured the absorbance profile of the acylated reagent with a number of electron-rich arenes of known ionization potential ( I p ), including naphthalene ( I p = 8.12 eV), 72 1,3,5-trimethoxybenzene ( I p = 7.96 eV), 73 and 2-methoxynaphthalene ( I p = 7.80 eV). 74 EDA complexes have a characteristically linear relationship between their charge-transfer absorbance energy (hν CT ∝ λ max ) and the ionization potential ( I p ) of the constituent donor.…”
Section: Resultsmentioning
confidence: 99%
“…The combination of 1, 2 , and TFAA (1:1:2 ratio; Figure 2A) revealed a strongly absorbing signal in the visible region, and we postulated that this new absorbance could be attributed to an electron donor-acceptor (EDA) interaction. 71 To probe this relationship further, we measured the absorbance profile of the acylated reagent with a number of electron-rich arenes of known ionization potential ( I p ), including naphthalene ( I p = 8.12 eV), 72 1,3,5-trimethoxybenzene ( I p = 7.96 eV), 73 and 2-methoxynaphthalene ( I p = 7.80 eV). 74 EDA complexes have a characteristically linear relationship between their charge-transfer absorbance energy (hν CT ∝ λ max ) and the ionization potential ( I p ) of the constituent donor.…”
Section: Resultsmentioning
confidence: 99%
“…[38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] We have also explored photoredox catalysis employing photofunctional complexes of Ru II ,I r III ,a nd Pt II ,a nd established the photoelectrochemical mechanismso ft he reductive actions of such complexes. Radical species canb ed erived from benzylh alidest hrough photoinduced reductived issociation.…”
Section: Introductionmentioning
confidence: 99%
“…11 Further studies revealed that white LED irradiation, the presence of base, and the absence of oxygen were each essential for this transformation (entries 2, 5, and 6). These control experiments suggest a radical mechanism involving thiyl and aryl radicals formed as a result of visible-light-promoted intermolecular charge transfer 12 that are subsequently quenched to yield the C–S cross-coupled product (vide infra).…”
mentioning
confidence: 99%